2005
DOI: 10.1002/ajh.20402
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of organ dysfunction in transfused patients with SCD or β thalassemia

Abstract: Although it is life saving, transfusion therapy has resulted in the majority of sickle cell anemia and thalassemia patients being at risk for hemosiderosis-induced organ damage. It is unknown whether the complications of iron overload are affected by the underlying disease. In order to address this problem, we compared the prevalence of organ dysfunction in both groups of patients receiving chronic transfusion therapy (b thalassemia, N = 30; sickle cell anemia, N = 43). Both groups had similar quantitative liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
114
1
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(126 citation statements)
references
References 23 publications
6
114
1
3
Order By: Relevance
“…1 Nevertheless, iron overload remains a common complication, especially after long-term treatment. 2,3 On the one hand, it has been evident from previous studies that iron overload is the main causative agent responsible for the increased production of free radicals and reactive oxygen species (ROS), and the subsequent oxidative stress which is compensated for by various antioxidants present in the body. 4 Oxidative stress occurs as a result of increased levels of lipid peroxides and free-radical intermediates, along with a decrease in total antioxidant capacity (TAC).…”
mentioning
confidence: 99%
“…1 Nevertheless, iron overload remains a common complication, especially after long-term treatment. 2,3 On the one hand, it has been evident from previous studies that iron overload is the main causative agent responsible for the increased production of free radicals and reactive oxygen species (ROS), and the subsequent oxidative stress which is compensated for by various antioxidants present in the body. 4 Oxidative stress occurs as a result of increased levels of lipid peroxides and free-radical intermediates, along with a decrease in total antioxidant capacity (TAC).…”
mentioning
confidence: 99%
“…9,12 For example, patients with thalassemia major transfused every 3 weeks require nearly 10 years to demonstrate cardiac iron loading. 13 Patients with sickle cell disease compared with thalassemia major patients with equal duration and magnitude of iron loading exhibit much less iron-related cardiotoxicity 14 and only ∼2.5% ultimately develop cardiac iron. 4 In contrast, patients with DiamondBlackfan anemia or congenital dyserythropoietic anemia receiving transfusions demonstrate cardiac iron deposition much earlier, within ∼2 years, 9 a difference attributable to their relatively higher NTBI levels.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, extensive studies in regularly transfused patients with b-thalassemia major have identified heart failure as the leading cause of death due to iron accumulation in the myocardium [43,44]. While cardiac decompensation and cardiomyopathy are known clinical manifestations in patients with SCD, magnetic resonance imaging (MRI) T2* evaluation of cardiac iron load in patients with SCD has indicated lower levels of iron accumulation despite similar transfusion burdens [42,45,46]. A similar situation is seen with iron overloadassociated endocrinopathy, which has been shown to be common in patients with b-thalassemia major but rarely reported in the population of patients with SCD [42,47].…”
Section: Commentarymentioning
confidence: 99%
“…The distribution and consequences of iron overload in patients with SCD have been shown to differ compared with patients with b-thalassemia major. Although the liver is the primary site of excess iron storage in both patients with SCD and b-thalassemia major, with LIC correlating significantly with the duration of transfusions, there are some disparities in the occurrence of organ injury [41,42]. Furthermore, extensive studies in regularly transfused patients with b-thalassemia major have identified heart failure as the leading cause of death due to iron accumulation in the myocardium [43,44].…”
Section: Commentarymentioning
confidence: 99%
See 1 more Smart Citation